The global prevalence of gallstones in pregnancy: a systematic review and meta-analysis - Salari, Nader; Hasheminezhad, Razie; Heidarisharaf, Parisa; Khaleghi, Ali Asghar; Azizi, Arezou Haji; Shohaimi, Shamarina; Mohammadi, Masoud (Elsevier Ireland, 2023)
Background: Gallstone disease is the second most common non-gynecological disease that may require surgical intervention during pregnancy. This study investigates the global prevalence of gallstones in pregnancy through a systematic review and meta-analysis. Methods: A systematic review and meta-analysis of studies that reported the global prevalence of gallstones in pregnancy was conducted. PubMed, Scopus, Web of Science, Embase, ScienceDirect, and Google Scholar were searched for studies published up to September 2022. Results: In a review of 31 studies with a sample size of 190,714 people, the I2 heterogeneity test showed high heterogeneity (I2 = 98.8%). Therefore, the random effects method was used to analyze the results. The prevalence of gallstones was reported as 3.6% (95% CI: 1.9–6.7%). The highest prevalence of gallstones by continent was reported in America, at 6.8% (95% CI: 4.2–10.8%). The Egger test showed no evidence of publication bias (p = 0.609). Conclusion: Based on the results of this study, health policymakers should emphasize to the target community and the medical staff dealing with pregnant women the importance of screening for gallstones during pregnancy.